The use of technology acceptance model on student behavior using e-money - Dedy Gunawan Manurung; Anne Rumondang Malau (Universitas Negeri Padang, 2021)
This research is a replication and development of the Technology Acceptance Model (TAM) in order to determine the effect of perceived usefulness and ease of use on interest of using OVO. The sample used in this research were 150 respondents using questionnaire and google doc. The results of this research conclude that perceived usefulness has a significant effect on interest in use while perceived ease of use has no significant effect on interest of use. Suggestions that can be given in this study are giving attractive promos such as discounted prices. As well as increasing collaboration with various merchants to facilitate and add value to the benefits of using OVO electronic money. And for ease of use, the problem that often occurs is failure in filling, therefore it is necessary to monitor and improve the quality of electronic money readers so that the problem can be resolved immediately.